Achieving robust and highly efficient nitrogen removal in a mainstream anammox reactor by introducing low concentrations of readily biodegradable organics - Yang, Yandong; Long, Yanan; Xu, Jiarui; Liu, Shichong; Liu, Lei; Liu, Changqing; Tian, Yong (Frontiers in Microbiology, 2023)
In this study, an anammox reactor was operated to treat low-strength (NH4+ + NO2-, 25–35 mg/L) wastewater without (phase I) or with (phase II) readily biodegradable chemical oxygen demand (rbCOD). In phase I, although efficient nitrogen removal was achieved at the beginning, nitrate accumulated in the effluent after long-term operation (75 d), resulting in a decrease in the nitrogen removal efficiency to 30%. Microbial analysis revealed that the abundance of anammox bacteria decreased from 2.15% to 1.78%, whereas that of nitrite-oxidizing bacteria (NOB) increased from 0.14% to 0.56%. In phase II, rbCOD, in terms of acetate, was introduced into the reactor with a carbon/nitrogen ratio of 0.9. The nitrate concentration in the effluent decreased within two days. Advanced nitrogen removal was achieved in the following operation, with an average effluent total nitrogen of 3.4 mg/L. Despite the introduction of rbCOD, anammox pathway still dominated to the nitrogen loss. High-throughput sequencing indicated that high anammox abundance (2.48%) further supports its dominant position. The improvement in nitrogen removal was attributed to the enhanced suppression of NOB activity, simultaneous nitrate polishing through partial denitrification and anammox, and promotion of sludge granulation. Overall, the introduction of low concentrations of rbCOD is a feasible strategy for achieving robust and efficient nitrogen removal in mainstream anammox reactors.